Memoria 1988-1989. - Galeria Arte Actual, Santiago de Chile (Santiago de Chile : Galeria Arte Actual, 1989)
Basso, Jose Esteban ; De la O., Patricio ; Diaz, Gonzalo ; Ferreiro, Antonia ; Figueroa, Patricia ; Gonzalez, Ida ; Irarrazaval, Mario ; Larenas, Mireya ; Larrain, Marcelo ; Lay, Sergio ; Toral, Mario ; Ulloa, Alejandro ; Valdivieso, Raul ; Zamudio, Enrique ; etc.
Spaans
boek